Semantic Ambiguity of ‘MAIN’ Word in Kompas.com News Articles 2025 - tanisha firyal; Rifa Nurfadilah; Tatu Siti Rohbiah (Journal of Literature Language and Academic Studies, 2026)
Purpose – This study aims to identify and analyze the semantic ambiguity of the word “main” in news articles published on Kompas.com throughout 2025. The study focuses on examining the lexical and contextual meanings of the word “main” as well as the differences and potential contradictions between those meanings in news discourse. The word was selected because it frequently appears in various journalistic contexts and demonstrates a high level of polysemy and contextual variation. Methodology – This study uses a qualitative approach with a descriptive method using semantic analysis. The data were collected from news articles published between January and December 2025 containing the word “main” in headlines or article contents. Data collection was conducted through documentation techniques by accessing Kompas.com and selecting relevant articles through purposive sampling. The research instruments included data classification sheets and analysis tables. The data were analyzed through data reduction, classification, interpretation, and conclusion drawing based on lexical, contextual, grammatical, and connotative meanings. Findings – The findings reveal that the lexical meaning of “main” as “to play” rarely appeared directly in the news discourse. Instead, the word frequently carried contextual meanings such as seriousness, warning, manipulation, violation, hidden relations, risk, and strategic actions. The study also found that ambiguity emerged due to polysemy, idiomatic expressions, grammatical variations, and contextual interpretation. Forms such as “main-main,” “main mata,” and “main api” significantly contributed to semantic ambiguity in journalistic language. Novelty – This study offers a specific semantic analysis focusing on a single polysemous word in Indonesian online news discourse. It emphasizes the relationship between lexical meaning, contextual meaning, and ambiguity in media language usage. Significance – This study is beneficial for linguistics researchers, media language analysts, journalists, educators, and readers who seek to understand contextual meaning and ambiguity in journalistic texts. It may also serve as a reference for further studies related to semantics and language use in mass media.